DERADIKALISASI SEMU: STRATEGI DERUTINISASI PENANGANAN SAMPAH ANALISIS STRUKTURASI DALAM ISU PENANGANAN SAMPAH DI KOTA BANDUNG OLEH WALIKOTA PERIODE 2013-2018 - Mustabsyirotul Ummah Mustofa (Universitas Padjadjaran, 2016)
This research is motivated by the condition of Bandung as the locus of research addressing the issue of waste, that is quite crucial, even Bandung has ever dubbed as “the city of pig” and “the city of waste”. The efforts to deal with the waste have been tried since the previous Mayor with radical way and that was by changing the viewpoints of waste by viewing the waste as valuable resources. But this effort was been deadlocked and even causing a con ict. Eventhough the deroutineness efforts on waste management has not been fully crystalized, basically the Mayor is on progress preparing more adequate capital and supporting structure. The Mayor makes as if the deradicalization efforts is a strategy to form capitals as a mean for real deroutineness waste management. This aims to get resources from the structure traces that he’s been created, in the form of public support that will help to have the postponed radicalization of waste agenda, which the real radicalization objective is essentially a clean city with modern waste management through the use of technology. This phemenon has marked that the reproduction af a new structure is a long and complicated process and requires a lot of precondition to reach the deroutineness goal.